Financing the Circular Future: How Gendered Access to Green Capital Shapes Women’s Participation in Circular Economy Enterprises - Afrianto Afrianto; Rukmuin Wilda Payapo; Fatmawati Fatmawati; Nur Azda; Ervan Togatorop; Simon Hendrik Leasa (Pattimura Proceeding, 2026)
The transition to a Circular Economy (CE) represents a critical pathway for sustainable development, yet the participation of women in CE enterprises remains constrained by systemic gendered barriers, particularly in access to specialized green finance. This study investigates how gendered access to green capital influences women’s engagement, decision-making, and scaling capacity in CE initiatives across Indonesia. Using survey data from 400 respondents and applying Structural Equation Modeling (SEM), the analysis examines the direct effects of institutional fairness and financial capability on women’s participation, as well as the mediating role of credit constraints. Findings reveal that equitable institutional frameworks and enhanced financial capabilities significantly increase women’s participation in CE enterprises, while limited access to green capital remains a critical barrier. The results underscore the importance of integrating gender-sensitive policies within climate finance mechanisms to ensure an inclusive and effective CE transition. This research contributes to the intersectional literature on gender, finance, and sustainability, offering actionable insights for policymakers, development practitioners, and financial institutions aiming to foster equitable green economic growth.